Taguchi Method Analysis of Machining Properties of Al-Slag/Flyash Hybrid Composite - Dr.M.MahendraBoopathi, R.Naveen Prabu , M.Vijayaraj , (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2022)
Metal Matrix Particulate Composites (MMPCs) have emerged as a promising material for automotive and aerospace applications. Metal Matrix Composites (MMCs) AA2024 have a wide range of applications in aerospace and automotive engineering. An attempt is made in this research work to investigate the machining qualities of the AA2024 MMCs. Slag and Fly-Ash elements were used as reinforcement during a two-stage stir casting method. The dry drilling test with the twit drill tool was investigated experimentally. The drill's optimal parameters have been determined. The thrust applied to the work piece when it was drilled was measured using a dynamometer.